To Compare the Outcome of Open Versus Laparoscopic Peritoneal Lavage in Patients With Primary Peritonitis Presenting in Surgical Emergency of SHZ Hospital, Rahim Yar Khan - Jahan, Yar; Ghafoor, Muhammad Tariq (Biological and Clinical Sciences Research Journal, 2025)
Primary peritonitis is a surgical emergency traditionally managed by open peritoneal lavage, though minimally invasive approaches are increasingly being adopted due to potential postoperative benefits. Objective: To compare the outcomes of open versus laparoscopic peritoneal lavage in patients with primary peritonitis in terms of wound infection, operative time, postoperative pain, and length of hospital stay. Methods: A randomized controlled trial was conducted in the Department of General Surgery, Sheikh Zayed Hospital, Rahim Yar Khan, from March to May 2025. A total of 160 patients of either gender, aged 18–60 years, diagnosed with primary peritonitis, were randomly assigned to undergo either open or laparoscopic peritoneal lavage. Demographic variables, operative time, postoperative pain, wound infection, and length of hospital stay were recorded. Categorical variables were analyzed using the Chi-square test, while continuous variables were compared using the Mann–Whitney U test. Statistical analysis was performed using SPSS version 26.0, with a P-value < 0.05 considered statistically significant. Results: Both groups were comparable with respect to age, body mass index, gender distribution, and ASA score. Operative time was significantly shorter in the laparoscopic group (P < 0.001), and hospital stay was shorter (P = 0.030). Postoperative pain scores were significantly lower in the laparoscopic group at 0, 4, and 8 hours postoperatively (P < 0.05). Mild wound infection (SWA Grade I) was more frequently observed in the laparoscopic group, whereas moderate to severe wound infections were significantly more common in the open surgery group (P = 0.011). Conclusion: Laparoscopic peritoneal lavage is a safe and effective alternative to open surgery for the management of primary peritonitis, offering shorter operative time, reduced postoperative pain, a shorter hospital stay, and a lower rate of clinically significant wound infections, supporting its role in emergency surgical practice.